The Effect of Standardized Interviews on Organ Donation - (:unkn) unknown (BASKENT UNIV, 2018)
Objectives: Organ donation is the most important stage for organ transplant. Studies reveal that attitudes of families of brain-dead patients toward donation play a significant role in their decision. We hypothesized that supporting family awareness about the meaning of organ donation, including saving lives while losing a loved one, combined with being informed about brain death and the donation process must be maintained by intensive care unit physicians through standardized interviews and questionnaires to increase the donation rate. Materials and Methods: We retrospectively evaluated the final decisions of families of 52 brain-dead donors treated at our institution between 2014 and 2017. Data underwent descriptive analyses. The standard interview content was generated after literature search results were reviewed by the authors. Previously, we examined the impact of standardized interviews done by intensive care unit physicians with relatives of potential brain-dead donors regarding decisions to donate or reasons for refusing organ donation. After termination of that study, interviews were done according to the intensivist's orientation, resulting in significantly decreased donation rates. Standardized interviews were then started again, resulting in increased donation rates. Results: Of 17 families who participated in standardized interviews, 5 families (29.4%) agreed to donate organs of their brain-dead relatives. In the other group of families, intensivists governed informing the families of donation without standardized interviews. In this group of 35 families, 5 families (14.3%) approved organ donation. The decision regarding whether to agree to organ donation was statistically different between the 2 family groups (P < .05). Conclusions: Conducting a standard interview between relatives of brain-dead donors and the intensivists, facilitating visits between relatives and the brain-dead patients, and informing relatives about the donation process resulted in an increased rate of organ donation compared with routine protocols.
Keywords: Attitudes and beliefs; Family discussion; Intensive care physician; Potential brain-dead donor; CONSENT